2017
DOI: 10.1007/s00280-017-3415-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term daily temozolomide with dose-dependent efficacy in MGMT promotor methylation negative recurrent high-grade astrocytoma

Abstract: Temozolomide (TMZ) for malignant gliomas is traditionally dosed in 5 out of a 28-day cycle, however alternative regimens exist, including dose-dense. Continuous daily dosing is available, but the acceptable dose and duration of therapy is unknown. We document a 40-year-old male with recurrent anaplastic astrocytoma, IDH mutant and MGMT promotor methylation negative, who has well-tolerated continuous daily TMZ for 20 months at 100 mg per day for nearly the length of this period. A trial at 80 mg per day demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…A meta-analysis has indicated that long-term treatment is more bene cial in terms of both OS and PFS [34]. In addition, according to one study, MGMT-mediated TMZ resistance may be attenuated by continuous therapy [35]. Certainly, long-term administration of TMZ would enhance the accumulation of TMZ in the body, and may have the same signi cance as the use of dose-dense TMZ, which depletes MGMT.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis has indicated that long-term treatment is more bene cial in terms of both OS and PFS [34]. In addition, according to one study, MGMT-mediated TMZ resistance may be attenuated by continuous therapy [35]. Certainly, long-term administration of TMZ would enhance the accumulation of TMZ in the body, and may have the same signi cance as the use of dose-dense TMZ, which depletes MGMT.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis has indicated that long-term treatment is more beneficial in terms of both OS and PFS [41]. In addition, according to one study, MGMTmediated TMZ resistance may be attenuated by continuous therapy [42]. Certainly, long-term administration of TMZ would enhance the accumulation of TMZ in the body, and may have the same significance as the use of dose-dense TMZ, which depletes MGMT.…”
Section: Discussionmentioning
confidence: 99%
“…Of those tested, only interleukin 11 (IL11) exhibited the anticipated survival association. In the TCGA dataset, high IL11 mRNA expression was associated with 9 poor survival ( Fig. 2D).…”
Section: Microglia-secreted Il11 Enhances Glioblastoma Tumorigenicitymentioning
confidence: 96%
“…First, while glioblastomas harboring isocitrate dehydrogenase (IDH) mutations are generally associated with improved survival (3), such mutations are not required for long-term survivorship (4,5). Second, in independent studies, clinical specimens from long-term survivors are more likely to harbor promoter methylation attenuating the expression of O6-methylguanine-DNA-methyltransferase (MGMT), a DNA repair protein that confers TMZ resistance (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%